2019
DOI: 10.1007/s11336-019-09662-9
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Foundations for Computerized Adaptive Testing with Response Revision

Abstract: The compatibility of computerized adaptive testing (CAT) with response revision has been a topic of debate in psychometrics for many years. The problem is to provide test takers opportunities to change their answers during the test, while discouraging deceptive strategies from their side and preserving the statistical efficiency of the traditional CAT. The estimating approach proposed in Wang et al. (Stat Sin 27(4):1987-2010, based on the nominal response model, allows test takers to provide more than one ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…To address the above concerns, researchers have proposed several methods to allow item review in CAT from different perspectives (Bowles & Pommerich, 2001; Han, 2013; Papanastasiou & Reckase, 2007; Stocking, 1997; S. Wang et al, 2019; Yen et al, 2012).…”
Section: Representative Methods For Reviewable Catmentioning
confidence: 99%
“…To address the above concerns, researchers have proposed several methods to allow item review in CAT from different perspectives (Bowles & Pommerich, 2001; Han, 2013; Papanastasiou & Reckase, 2007; Stocking, 1997; S. Wang et al, 2019; Yen et al, 2012).…”
Section: Representative Methods For Reviewable Catmentioning
confidence: 99%
“…Hence, changing responses retrospectively may impact the measurement precision, which results in larger standard errors [69,[73][74][75][76][77][78]. Therefore, allowing item revision within CATs has been controversially discussed in the literature, even if some contributions encountered this measurement problem (see, e.g., [66,77,[79][80][81][82]). While it can be argued that only a few persons might change their responses [83], a lack of this ability appears to contribute to increased test anxiety.…”
Section: Test Anxietymentioning
confidence: 99%
“…In this way, Wang et al (2017) showed that the resulting ability estimator preserves the asymptotic efficiency of the conventional CAT when the number of revisions is small relative to the number of items. Wang et al (2019) further reformulated this conditional estimation approach and extended the theoretical results to a larger class of IRT models. In addition, an equal-weight estimation approach, which is an ad hoc modification of the original Wang et al (2017) conditional estimation method, was proposed to deal with response revision with dichotomous IRT models.…”
Section: Introductionmentioning
confidence: 99%
“…These two ability estimation methods in Wang et al (2017, 2019) essentially assign a weight to each distinct answer of the same item in a deterministic way. For the conditional estimation method, the weight for the initial weight and any subsequent revisions is determined automatically through the score function, and the initial answer always carries a larger weight compared with the revisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation